2013
DOI: 10.1021/cm304123s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Graphite Source on Chemical Oxidative Reactivity

Abstract: Although all graphites share the same idealized chemical structure, marked differences in fact exist between their reactivities, such as the propensity for oxidation, that need to be taken into consideration for the development of applications. Here we show that five different commercially sourced natural and synthetic graphites differ significantly in their response to a modified Staudenmaier oxidation that produces substoichiometric graphene oxides (sub-GOx). The dominant oxidation product is hydroxyl groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Natural graphite (NG) is widely present on Earth, especially in the northeast of China, and it has a good conductivity and layered structure. Expandable graphite (EG) is derived from NG after a simple treatment; as EG has a larger interlayer distance than NG, some functional composites can be introduced into the interlayer of NG [42,43]. Based on these considerations, in a previous study, we synthesized mesoporous carbon/graphite nanosheet composites by intercalating resol prepolymer into the EG interlayer, followed by the exfoliation of EG through in situ polymerization and carbonization processes [44].…”
Section: Introductionmentioning
confidence: 99%
“…Natural graphite (NG) is widely present on Earth, especially in the northeast of China, and it has a good conductivity and layered structure. Expandable graphite (EG) is derived from NG after a simple treatment; as EG has a larger interlayer distance than NG, some functional composites can be introduced into the interlayer of NG [42,43]. Based on these considerations, in a previous study, we synthesized mesoporous carbon/graphite nanosheet composites by intercalating resol prepolymer into the EG interlayer, followed by the exfoliation of EG through in situ polymerization and carbonization processes [44].…”
Section: Introductionmentioning
confidence: 99%
“…No relationship was found between the defect density of the starting graphite and the extent of oxidation of GO, as suggested by ap revious study. [33] Instead, ad irect correlationb etween the purity of the starting natural graphite and extent of oxidation of the resultant GO was observed. Small quantities of sulfur and nitrogen were also present in the GOs, and arose from covalently bondedo rganosulfates, inorganic sulfates, and/or residual adsorbed sulfuric and nitric acid during synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, due to the inherent defects and complexity of the structure, the precise oxidation mechanism in those reactions is hard to elucidate. Chen et al observed that the product from the highest crystallinity graphite offers best transport for electrons and holes [ 28 ]. Kim et al also prepared GO from three different graphite sources with modifi ed Hummer's method and observed disparities in sheet size distributions [ 30 ].…”
Section: Discussionmentioning
confidence: 99%